The advances in DNA mixture interpretation. (August 2019) - Yang, Jiawen; Lin, Donghai; Deng, Chuwei; Li, Zheng; Pu, Yan; Yu, Yanfang; Li, Kai; Li, Ding; Chen, Peng; Chen, Feng
Highlights: The recent advances in interpreting DNA mixture were reviewed. Several different genetic marker used in DNA mixture analysis were reviewed. The challenges and future of individual identification from DNA mixture were summarized and discussed. Abstract: In forensic genetics, the analysis of DNA in biological samples is a valuable tool for personal identification. There is an increasing demand in analyzing of the mixed DNA which may provide insightful investigative instructions. With the continuous effort for the improvement of individual identification, complicated mixed stains represent a growing fraction of the samples processed by forensic laboratories. Recent technological advances have enabled quantitative analysis of DNA mixture and emerging sequencing approaches to decipher the complicated DNA mixture. Here, we describe the use of different genetic markers, typing approaches and analytical methods in mixture analysis, and how useful information can be obtained from complicated DNA mixture.